Real Time Monitoring and the New Information Technologies - Lucas, Henry; Batchelor, Simon; Berdou, Evangelia (IDS Bulletin, 2013)
Debates as to the potential role of new Information and Communication Technologies (ICTs) in monitoring the wellbeing of vulnerable groups i s often bedevilled by the failure of two principal actors – social res earchers and technical experts – to address the other’s concerns or ev en to use language that is comprehensible to the other side. The aim h ere is to unpick some of the technical language relevant in this conte xt and provide a brief introductory guide to some aspects of the curre nt, rapidly changing and highly diverse ICT environment.